PEMBELAJARAN JEROME BRUNER UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Asep Sutiadi (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2008)
Jerome Bruner’s learning (JBL) is one of teaching method that make student active in learning or studentcenter learning with three process, i.e. (i) information, (ii) transformation, and (iii) evaluation. Researchmethod is quasi-experiment and designed by one group time series with fewer samples class 8 of SMP’sstudent. The JBL was implementation in three times respectively. The research aim are to know theincreasing of student achievement and effectiveness after applied the JBL in three study result catagories, i.e.low, medium, and high. Result of research indicates that student’s cognitive is good at all categories (α =0.05). Percentages of student’s affective and psychomotor are good catagory. Effectiveness of study is hightoo at low, medium, and high student’s achievement catagories.Key word : Jerome Bruner’s Learning